Analysis of the determinants of domestic maize prices in Kenya - Kilwake, Pamela (Strathmore University, 2021)
The pricing of maize in Kenya has been the subject of much discussion over previous years. Various stakeholders in the industry (farmers, millers, regulators) offer often conflicting ideas on the factors that are deemed pivotal to the determination of maize prices. The current study sought to analyse the determinants of domestic maize prices in Kenya. The research was grounded on the law of supply and demand theory. The research relied on a quantitative approach grounded on an explanatory research design. The study utilized time series from 1990 -2019. This study relied on secondary research data. The study relied on time series collected from secondary sources of data using data extraction forms to obtain the maize price in Kenya. The data collected was analysed using descriptive statistics and inferential analysis. The results were presented using bar graphs, charts, and tables as deemed adequate for this study. The study was able to obtain all the 210 observation from the Central Bank of Kenya, World Bank Data and Kenya National Bureau of statistics. The correlation tests showed that macroeconomic factors, maize import and export quantity, land acreage under maize cultivation and maize production had a positive and significant correlation with domestic maize prices. The results also showed that maize export quantity had a positive but insignificant correlation with domestic maize prices. Regression analyses was carried out to determine the relationship between the study variables. The regression results indicated that 80.28% of the domestic maize prices in Kenya were determined by GDP growth, exchange rate variations, maize import quantity, maize export quantity, annual land acreage and annual quantity produced. The research also found out that GDP growth and maize export quantity did not have a statistically significant influence on domestic maize prices. The study concluded that exchange rate variation, maize quantity produced and maize import quantity had a positive and significant influence, while land acreage under maize cultivation had a significant and negative influence on the domestic maize prices. The research recommends that the government should incentivize local farmers to improve their maize production and reduce reliance on maize imports. Further the study recommends that local farmers should improve their investment in modern agriculture which can translate most small-scale farmers to large-scale farmers which can enhance the maize yield and foster their competitiveness within the global maize market.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Domestic maize prices_Kenya; Farmers; Millers; Regulators